Smart energy harvesting utilizing flow-induced techniques - Zhang, Guangcheng (2018)
The flow-induced vibration is one of the most common vibrational phenomena in the ambient environment, on which the previous studies were mainly dealing with methodologies as to how to control and reduce vibrations of objects in the flow field.